O PNAIC pré-escola e a formação de professoras e de crianças como leitoras de literatura - Maria do Carmo Rezende dos Santos Assunção de Oliveira (2022)
This work has as general objective to analyze, from the perspective of the professionals participating in the training action coordinated by the Universidade do Estado de Minas Gerais, the influence of the National Pact for Literacy in the Right Age Preschool in their training as readers of literature and in their pedagogical practices aimed at training children as readers of literature. The scope of this objective is linked to the following specific objectives: to describe the training context, based on the analysis of documents issued by the federal, state and local bodies; to characterize the training in the State of Minas Gerais, in the municipalities coordinated by the University, as to its scope in relation to the public reached; analyze how the course participants evaluated the suitability and potential of the material adopted in the course; to highlight the teachers' perception regarding the incidence of actions in their training as readers of literature and as mediators and promoters of literary reading with children; to develop an educational resource in order to offer a new training opportunity and contribute to the personal and professional development of Early Childhood Education teachers. A bibliographic research was carried out to identify academic productions that present an interface with this investigation. This research adopted a qualitative approach and used, as instruments for data collection, document analysis, the survey of quantitative data and the application of the questionnaire that is based on the assumptions of the material adopted in training, the Reading and Writing Collection in Early Childhood Education, seeking to evidence an articulation of the theoretical conceptions of this material with the practice of the course participants participating in this research. The results show that the National Pact for Literacy in the Right Age Preschool focused on the training of the responding teachers as readers of literature. In their daily practices, there was a lower incidence of responses focused on the family-school relationship. Regarding the importance exercised in the formation of the young reader, the respondents point to criteria that are close to the conceptions of the material that guided the formation and, in an antagonistic way, they also highlighted other criteria that are far from what is expected in their daily practices. With regard to the influence of training on their pedagogical practices, improvement prevails and not change in the sense of replacing a practice. It is clear, therefore, that the training generated a partial impact on their practices. Although they have good working conditions, have an adequate degree of training and have participated in the training, they have not shown that they have appropriated basic knowledge to ensure good mediation. As for the adequacy of the material intended for training, it can be seen that all the Notebooks marked the trajectory of the respondents. We emphasize, however, that Caderno 7, material that directly dialogues with issues related to the composition of collections, the structuring of reading spaces and literary mediation, was the one that left the least marks. The research indicates that, despite all the challenges, inconsistencies and tensions that were faced, the National Pact for Literacy in the Right Preschool Age carries the fundamental principles for an adequate professional development policy. It was a relevant initiative, although it was not enough, to think about the professional development of Early Childhood Education teachers.